Network sanctorum: reflections on an image of church online - Oorschot, Frederike van (Cursor_, 2023)
We must consider: how does the image of the network relate to other ecclesiological descriptions of the church? I propose we sharpen the image of the network in order to clarify its ecclesiological potentials and limits. This is of particular interest because the "network" is widely discussed not only in the field of digital church life but also in practical theology with a view to analog and digital church life. In the context of this conference and referring to the broad oeuvre of Heidi Campbell on this issue I will primarily focus on the debate about digital ecclesiology in the broader field of digital theology.